ANALYSIS OF THE DETERMINANTS OF THE HUMAN DEVELOPMENT INDEX (HDI) OF SUNGAI PENUH CITY AS SEEN IN THE FRONT OF ECONOMIC GROWTH, PUBLIC SECTOR EXPENDITURE, AND UNEMPLOYMENT RATE - Dewi Ernita; Silvia Rahayu; Osi Hayuni Putri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the factors that influence the Human Development Index (HDI) in Sungai Penuh City during the period 2013–2024. The independent variables studied include Economic Growth, Public Sector Expenditure (Capital), and the Open Unemployment Rate (TPT). The method used is a quantitative approach with a multiple linear regression model using secondary data sourced from the publication of the Central Statistics Agency (BPS). The results show that Economic Growth has a positive and significant effect on the HDI, while Public Sector Expenditure (Capital) has a negative but significant effect on the HDI. Meanwhile, the Open Unemployment Rate does not have a significant effect on the HDI. Simultaneously, the three independent variables have a significant effect on the HDI with a coefficient of determination of 98.01%, indicating that the model is able to explain variations in the HDI very strongly. This finding emphasizes the importance of improving the quality of economic growth and the efficiency of capital expenditure allocation as well as strengthening the employment sector as an effort to increase the HDI in Sungai Penuh City.